The association of Angelman's syndrome with deletions within 15q11-13. Issue 2 (February 1989) - Pembrey, M; Fennell, S J; van den Berghe, J; Fitchett, M; Summers, D; Butler, L; Clarke, C; Griffiths, M; Thompson, E; Super, M
Abstract : The inheritance of Angelman's syndrome, a disorder characterised by mental retardation, epilepsy, ataxia, and a happy disposition, is debated because affected sibs occur less frequently than expected with autosomal recessive inheritance. After discovering two unrelated patients with a small deletion of the proximal long arm of chromosome 15, 10 further patients with Angelman's syndrome were reassessed. Five had apparently normal karyotypes, four had a deletion within 15q11-13, and one had a pericentric inversion, inv(15)(p11q13) involving the same chromosomal region. In the latter case, the healthy mother had the same pericentric inversion, indicating that the patient also had a submicroscopic mutation on his other chromosome 15. These data map the Angelman locus to 15q11-13 and suggest that de novo visible deletions (associated with a low recurrence risk) and autosomal recessively inherited cases combine to give an overall sib recurrence risk of less than 25%.